Patellar Tendon Imbrication Is a Safe and Efficacious Technique to Shorten the Patellar Tendon in Patients With Patella Alta. Issue 10 (27th October 2020) - Patel, Ronak M.; Gombosh, Michael; Polster, Joshua; Andrish, Jack
Background: Patella alta has been noted to be a risk factor for recurrent patellar instability. Purpose: We conducted a radiographic study to determine whether a patellar tendon imbrication technique normalizes patellar height as well as whether the shortened length is maintained at a minimum 2-year follow-up. Study Design: Case series; Level of evidence, 4. Methods: A total of 54 consecutive patients were identified after a retrospective chart review was performed on patients who underwent patellar tendon imbrication between 2008 and 2013. Preoperative, 3 weeks postoperative, and minimum 2 years postoperative lateral radiographs were analyzed using Insall-Salvati (IS), Blackburne-Peel (BP), and Caton-Deschamps (CD) indices to determine the amount of shortening that was achieved after the procedure and to what degree that shortening was maintained at a minimum 2-year follow-up. Results: A total of 27 patients (32 knees) completed a minimum 2-year follow-up. The mean patellar tendon length preoperatively was 6.1 cm (range, 5-8 cm). At 3 weeks and 2 years, the mean tendon lengths were 5.1 and 5.2 cm, respectively. Thus, the mean ± SD change in patellar tendon length from preoperative to 3 weeks postoperative was 0.97 ± 0.67 cm. IS, BP, and CD ratios had minimal change (loss of correction) from 3-week to 2-year follow-up; the delta values were 0.04, –0.03, and 0.09, respectively. There were no complications directly related to the technique. Conclusion: Patellar tendon imbrication is a safe and effective procedure to correct patella alta in the setting of lateral patellar instability. On average, the technique allowed 1 cm of patellar tendon shortening and maintained the correction at a minimum 2-year follow-up. In the skeletally immature patient, this technique allows correction of patella alta by avoidance of a tibial tuberosity osteotomy.